Scene classification for aerial images based on CNN using sparse coding technique - Qayyum A.; Malik A.S.; Saad N.M.; Iqbal M.; Faris Abdullah M.; Rasheed W.; Rashid Abdullah T.A.; Bin Jafaar M.Y. (Taylor and Francis Ltd., 2023)
Antennas; Classification (of information); Codes (symbols); Convolution; Image classification; Neural networks; Remote sensing; Satellite imagery; Semantics; Unmanned aerial vehicles (UAV); Convolutional Neural Networks (CNN); Future applications; High resolution remote sensing imagery; Mid-level features; Multi-scale features; Robust performance; Scale invariant feature transforms; Scene classification; Image coding; aircraft; artificial neural network; image classification; satellite imagery; unmanned vehicle